Understanding the effects of gamma‐irradiation on potassium levels in red cell concentrates stored in SAG‐M for neonatal red cell transfusion. Issue 2 (8th September 2014) - Winter, K. M.; Johnson, L.; Kwok, M.; Reid, S.; Alarimi, Z.; Wong, J. K. L.; Dennington, P. M.; Marks, D. C.
<x xml:space="preserve">Abstract</x> Background and Objectives Red cell transfusions, to paediatric patients, are often gamma‐irradiated to prevent transfusion‐associated graft‐versus‐host disease. This study measured changes in potassium and other in vitro parameters immediately following gamma‐irradiation of paediatric and full‐size red cell concentrates (RCCs). Materials and Methods The effects of irradiation on potassium release in RCCs stored in SAG‐M were investigated under three scenarios. In the first scenario, RCC < 5 days was split into paediatric packs, gamma‐irradiated and tested for potassium and haemolysis at 0, 2, 4, 6, 24 and 48 h. In the second scenario, full‐size RCCs < 5 days postcollection were gamma‐irradiated and tested as for the paediatric packs. Thirdly, RCCs < 14 days postcollection were gamma‐irradiated and assessed at 6 and 24 h and 7 and 14 days. Each group contained paired controls that were not gamma‐irradiated. Results In all situations, gamma‐irradiation resulted in a twofold increase in potassium concentrations after 24 h of storage, compared to matched unirradiated controls. This difference was detectable as early as 2 h postirradiation. Few differences were observed between control and irradiated RCCs in other key parameters, including ATP, 2, 3‐DPG, haemoglobin, pH, glucose and lactate concentration. Conclusion Gamma‐irradiation of RCCs significantly increased extracellular potassium. Irradiation of fresher RCCs results in lower potassium concentrations, which is less likely to lead to hyperkalaemia upon transfusion.